2010
DOI: 10.1123/jcsp.4.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Burnout Among Adolescent Female Gymnasts: Three Case Studies

Abstract: Within the current study, the process of adolescent burnout is considered in relation to perceived contributors, symptoms, consequences, and subsequently, effective and ineffective coping strategies. Through case studies, the researchers sought the burnout experiences of three competitive female gymnasts. Participants were selected based on scores obtained from Raedeke and Smith’s (2001) Athlete Burnout Questionnaire. To gain a comprehensive understanding of the process, athlete data were considered in tandem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Such recommendations were raised because of some research findings which demonstrated that sport specialization with high-intensity in adolescence may lower proper healthy growth and cause a lot of problems, such as a higher risk of overuse injuries, emotional stress, and burnout ( Brad & Stern, 2014 ; Gould, 2009 ; Russell & Limle, 2013 ). Similar results were shown in studies on individuals from diverse sport specialization demonstrating that early sport specialization brought a negative influence on the mental health of adolescents ( Dubuc et al, 2010 ; Martinent et al, 2014 ; Schmikli et al, 2011 ).…”
Section: Introductionsupporting
confidence: 85%
“…Such recommendations were raised because of some research findings which demonstrated that sport specialization with high-intensity in adolescence may lower proper healthy growth and cause a lot of problems, such as a higher risk of overuse injuries, emotional stress, and burnout ( Brad & Stern, 2014 ; Gould, 2009 ; Russell & Limle, 2013 ). Similar results were shown in studies on individuals from diverse sport specialization demonstrating that early sport specialization brought a negative influence on the mental health of adolescents ( Dubuc et al, 2010 ; Martinent et al, 2014 ; Schmikli et al, 2011 ).…”
Section: Introductionsupporting
confidence: 85%
“…Youth athletes are increasingly being exposed to inappropriate and unrealistic demands and expectations, and consequent psychological overload (self or coach/parent induced) 54 60. How youth athletes perceive and cope with these stressors is neither predictable nor benign,131 with athlete burnout and subsequent related drop-out from sport being a recognised part of competitive youth sport 132. Use of performance-based field criteria (eg, resting cortisol levels and Profile of Mood test) may facilitate early detection of youth at risk of burnout 133.…”
Section: Challenges To Health Well-being and Performancementioning
confidence: 99%
“…and were scored on a five-point Likert scale ranging from one (almost never) to five (almost always). The ABQ was chosen as a burnout measure due to its acceptable psychometric properties and its predominant use to assess burnout in sport Dubuc et al, 2010;Gustafsson et al, 2008;Hodge et al, 2008;Lemyre et al, 2006). Raedeke and Smith (2001) reported that the internal consistency of the subscales exceeds .70 and testretest reliability coefficients range from .86 to .92 on the three subscales.…”
Section: Instrumentmentioning
confidence: 99%